Design and performance study of a rotating piezoelectric wind energy harvesting device with wind turbine structure. (1st October 2022) - He, Lipeng; Han, Yuhang; Liu, Renwen; Hu, Renhui; Yu, Gang; Cheng, Guangming
Abstract: This paper proposes a rotating piezoelectric ambient wind energy harvesting device with wind turbine structure (R-PWEH), which mainly consists of wind turbine, support structure, excitation module, and power generation unit. This paper mainly investigates the effect of wind turbines with a different number of fan blades and units with different shapes of power generation on the performance output of R-PWEH. A series of experimental studies were conducted on the R-PWEH in the wind speed range of 0–20 m/s. In the experimental study at a wind speed of 16 m/s, the maximum voltage output of the R-PWEH was 114.24 V when the wind turbine with 11 fan blades and the rectangular cantilever beam power generation unit was installed. The optimal external load at this point is 8 kΩ and the maximum output power is 36.89 mW. The fastest charging rate for the capacitor at this parameter allows for easy powering of multiple light-emitting diodes for illumination. It has good prospects for development in practical applications, such as the ability to power micro and small sensors. Highlights: The wind turbine can better collect wind energy from the environment. The use of excitation rod improves overall power generation efficiency. The effects of different cantilever shapes on R-PWEH are analyzed in detail. Hermetically sealed housing improves overall environmental adaptability. It can supply power for micro-electronic devices.